2013
DOI: 10.4014/jmb.1308.08007
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Novel Agar-Degrading Marine Bacterium, Gayadomonas joobiniege gen, nov, sp. nov., from the Southern Sea, Korea

Abstract: An agar-degrading bacterium, designated as strain G7(T), was isolated from a coastal seawater sample from Gaya Island (Gayado in Korean), Republic of Korea. The isolated strain G7(T) is gram-negative, rod shaped, aerobic, non-motile, and non-pigmented. A similarity search based on its 16S rRNA gene sequence revealed that it shares 95.5%, 90.6%, and 90.0% similarity with the 16S rRNA gene sequences of Catenovulum agarivorans YM01(T), Algicola sagamiensis, and Bowmanella pacifica W3-3A(T), respectively. Phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Likewise, Glaciecola agarilytica dominated an agar-degrading community ( Wietz et al, 2015 ) in accordance with the agarolytic phenotype reported for this bacterium ( Yong et al, 2007 ). Several other genera within the Alteromonadaceae family have been connected with agarolytic activities such as Agarivorans ( Kim et al, 2016 ), Gayadomonas ( Chi et al, 2013 ), and Catenovulum ( Yan et al, 2011 ), however, little is known about the responsible enzymatic systems within these taxa. Paraglaciecola hydrolytica S66 T represents a newly isolated Gammaproteobacterium of the Alteromonadaceae family, which has the ability to degrade both agar and carrageenan ( Bech et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Glaciecola agarilytica dominated an agar-degrading community ( Wietz et al, 2015 ) in accordance with the agarolytic phenotype reported for this bacterium ( Yong et al, 2007 ). Several other genera within the Alteromonadaceae family have been connected with agarolytic activities such as Agarivorans ( Kim et al, 2016 ), Gayadomonas ( Chi et al, 2013 ), and Catenovulum ( Yan et al, 2011 ), however, little is known about the responsible enzymatic systems within these taxa. Paraglaciecola hydrolytica S66 T represents a newly isolated Gammaproteobacterium of the Alteromonadaceae family, which has the ability to degrade both agar and carrageenan ( Bech et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A Novel Agarase (AgaJ5) of G. joobiniege G7 There are 12 putative agarase genes in G. joobiniege, a marine bacterium with strong agar-degrading ability [30]. Among them, we have characterized two novel β-agarases, AgaJ9 and AgaJ11 [3,27].…”
Section: Resultsmentioning
confidence: 99%
“…The 16S rRNA gene sequence of G. joobiniege G7 shows 95.5% similarity with that of Catenovulum agarivorans YM01 [30,31]. The whole-genome sequence revealed 12 putative agarase genes belonging to GH16, GH39, GH42, and GH86 [30,31]. Among them, two β-agarases were biochemically characterized.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Agar oligosaccharides (AOS) produced by agarase has a good application prospect. Agar, a marine polysaccharide producing from red algae, is widely used in food industry, pharmaceutical industry and biological engineering ( Won-Jae et al, 2013 ). As the main component of agar, agarose is composed of 3,6-anhydro-L-galactose (L-AHG) and D -galactose (D-Gal) bonded alternately by α-1,3 and β-1,4 linkages ( Araki, 1956 ).…”
Section: Introductionmentioning
confidence: 99%